2‐Arachidonoylglycerol‐mediated endocannabinoid signaling modulates mechanical hypersensitivity associated with alcohol withdrawal in mice. (12th October 2022) - Morgan, Amanda; Adank, Danielle; Johnson, Keenan; Butler, Emily; Patel, Sachin
Abstract: Background: Alcohol use disorder (AUD) commonly occurs in patients with chronic pain, and a major barrier to achieving abstinence and preventing relapse is the emergence of hyperalgesia during alcohol withdrawal. Elucidating novel therapeutic approaches to target hyperalgesia associated with alcohol withdrawal could have important implications for treating AUD. Here, we examined the role of 2‐arachidonoylglycerol (2‐AG)‐mediated endocannabinoid (eCB) signaling in the regulation of hyperalgesia associated with alcohol withdrawal in mice. We tested the hypothesis that pharmacological augmentation of 2‐AG signaling could reduce hyperalgesia during withdrawal. Methods: Male and female C57BL/6J mice were tested during withdrawal from a continuous access two‐bottle choice (2BC) paradigm to investigate how eCB signaling modulates mechanical and thermal sensitivity during withdrawal. Mice were pretreated with the monoacylglycerol lipase (MAGL) inhibitor JZL184 to elevate levels of 2‐AG. Rimonabant or AM630 were given to block CB1 and CB2 receptor activity, respectively. DO34 was given to reduce 2‐AG by inhibiting the 2‐AG synthetic enzyme diacylglycerol lipase (DAGL). Results: After 72 h of withdrawal, male and female mice exhibited increased mechanical, but not thermal, hypersensitivity, which normalized by 7 days. This effect was reversed by pretreatment with JZL184. The effects of JZL184 were prevented by coadministration of either the CB1 or the CB2 antagonist. DO34, Rimonabant, and AM630 exacerbated mechanical hypersensitivity during alcohol withdrawal, causing an earlier onset and persistent hypersensitivity even 1 week into withdrawal. Conclusions: Our findings demonstrate the critical role of 2‐AG signaling in the bidirectional regulation of mechanical sensitivity during alcohol withdrawal, with enhancement of 2‐AG levels reducing sensitivity, and inhibition of 2‐AG signaling exacerbating sensitivity. These data suggest that 2‐AG augmentation represents a novel approach to the treatment of alcohol withdrawal‐associated hyperalgesia and AUD in patients with comorbid pain disorders. Abstract : The endocannabinoid 2‐Arachidonoylglycerol bidirectionally regulates mechanical hypersensitivity associated with alcohol withdrawal in mice. Systemic pharmacological enhancement of 2‐AG levels with the MAGL inhibitor JZL184 reduces mechanical hypersensitivity during alcohol withdrawal, and the effect of MAGL inhibition is prevented when blocking both CB1 and CB2 receptors. Furthermore, preventing synthesis of 2‐AG with a systemic pharmacological inhibitor of DAGL exacerbates sensitivity during alcohol withdrawal. These data suggest 2‐AG augmentation could represent a novel approach to the treatment of alcohol withdrawal‐associated hyperalgesia and AUD in patients with comorbid pain disorders.